A Slow ATP-induced Conformational Change Limits the Rate of DNA Binding but Not the Rate of β Clamp Binding by the Escherichia coli γ Complex Clamp Loader - Thompson, Jennifer A. (American Society for Biochemistry and Molecular Biology, 2009)
In Escherichia coli, the γ complex clamp loader loads the β-sliding clamp onto DNA. The β clamp tethers DNA polymerase III to DNA and enhances the efficiency of replication by increasing the processivity of DNA synthesis. In the presence of ATP, γ complex binds β and DNA to form a ternary complex. Binding to primed template DNA triggers γ complex to hydrolyze ATP and release the clamp onto DNA. Here, we investigated the kinetics of forming a ternary complex by measuring rates of γ complex binding β and DNA. A fluorescence intensity-based β binding assay was developed in which the fluorescence of pyrene covalently attached to β increases when bound by γ complex. Using this assay, an association rate constant of 2.3 × 10(7) m(−1) s(−1) for γ complex binding β was determined. The rate of β binding was the same in experiments in which γ complex was preincubated with ATP before adding β or added directly to β and ATP. In contrast, when γ complex is preincubated with ATP, DNA binding is faster than when γ complex is added to DNA and ATP at the same time. Slow DNA binding in the absence of ATP preincubation is the result of a rate-limiting ATP-induced conformational change. Our results strongly suggest that the ATP-induced conformational changes that promote β binding and DNA binding differ. The slow ATP-induced conformational change that precedes DNA binding may provide a kinetic preference for γ complex to bind β before DNA during the clamp loading reaction cycle.